(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
Crude leaf extracts of Andrographis paniculata Burm. f. showed significant inhibition of growth and mutagenesis of N. crassa. Result showed that 1 ml extract can react with the test organism, Neurospora crassa very easily. During the period of 24 hours, it produced only 1.8 cm linear vegetative growth of the mycelia. Whereas 1 ml and 0.50 ml extracts produced less reactions (2.95 and 3.15 cm. respectively). The linear growth decreased with the increase of the concentrations of the extracts. Conidia of Ema (5297) of N. crassa were treated for 3-4 hours separately in 100% and 50% concentration of the extracts. One hundred percent extracts produced four types of mutants, namely- dirty, ropy, albino, and buff and 50% extracts produced three types of mutants, namely- plug, ropy (thin) and conidial brand. Key words: Neurospora crassa, Andrographis paniculata, Mutants, Dirty, Ropy, Albino, Buff, Plug, Ropy (thin) and Conidial brand. DOI: 10.3329/bjsir.v43i2.960 Bangladesh J. Sci. Ind. Res. 43(2), 173-182, 2008